Financing An Office Development - Abu Zarin, Hasmah; Bujang, Ahmad Ariffian (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1998)
The issue of financing is very important for developers and real estate professionals. This issue has becoming more serious during the economy slowdown. The developers and the real estate professionals are in doubt on how to finance an 200,000 sq. ft. office development in major city such as Kuala Lumpur. Once they know how to finance this major development, they will have the confidence to carry out the office development effectively and efficiently.